Do knowledge management capabilities reduce the negative effect of environment uncertainties on organizational performance? A study of public listed companies in Malaysia - Alaarj S.; Mohamed Z.A.; Bustamam U.S.A. (Serials Publications, 2024)
Indexed by SCOPUS